Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I have a function $c(t,\lambda)$ with

$$\frac{\text dc}{\text dt}=f(c,\lambda),$$


$$\left(\frac{\text dc}{\text dt}\right)(t,\lambda)=f(c(t,\lambda),\lambda),$$

How to compute $$\frac{\text d}{\text dt}\left(\frac{\partial c}{\partial \lambda}\right)\ ?$$

Or more importantly why/how?

share|cite|improve this question
If $\lambda$ is not a function of $t$, you still should use partial derivative w.r.t. $t$ – Ilya Feb 14 '12 at 13:30
I think I have addressed the how in my post. For the why, one must first remember that this is a weird kind of self-referential (but certainly not artificial) problem...because it's a differential equation. With that in mind, ponder the diagram below, and then look at the forms that the derivatives take, i.e. the subscripts of $c$ and $f$ in the partials used. These are given functions, with fixed properties like their partial derivatives (with respect to their nominal arguments). But total derivatives require the chain rule & account for all formal arguments of the differentiated quantity. – bgins Feb 14 '12 at 23:57
just out of curiosity, where did this problem come from? – bgins Feb 15 '12 at 0:05
If $\lambda$ is a model parameter, then $\lambda'=0$ so that $c'=c_t$, $c'=f(c,\lambda)$ becomes a PDE not an ODE, and the inferred (a posteriori) formula for $c_{\lambda}$ in my post is invalid. In this case, I think the answer would be the first "unused" equation mentioned near the end of my post, i.e. $(c_{\lambda})'=c_{\lambda t}$, bringing us back to @il-y-a's comment. – bgins Feb 15 '12 at 8:32
up vote 1 down vote accepted

Let primes denote total derivatives with respect to $t$ and subscripts denote partial derivatives, so that $t_\lambda=\lambda_t=0$ but $\lambda'=\frac{d\lambda}{dt}$ is "irreducible" (and not necessarily zero), and assume that all derivatives below exist. Given the equation $$ c'=\frac{d}{dt}c(t,\lambda)=f(c,\lambda) $$ for the total derivative of $c$ with respect to $t$, note that (a priori) $$ dc =\frac{\partial c}{\partial t}dt +\frac{\partial c}{\partial \lambda}d\lambda \quad\implies\quad c'=c_t+c_\lambda\lambda' $$ which in our case (a posteriori), i.e. from $f=c'$, implies that $$ \frac{\partial c}{\partial \lambda} =c_\lambda=\frac{c'-c_t}{\lambda'} =\frac{f-c_t}{\lambda'}. $$ Although $c_t$ and $c_\lambda$ are, like $c(t,\lambda)$, functions of the independent variables $t$ and $\lambda$, they nevertheless also satisfy a constraint with respect to the the total derivative. This is true a priori. However, in our case, we are given that $c$ satisfies an ordinary differential equation with respect to time, i.e. the total derivative of $c$ with respect to "time" $t$ is itself a function $f$ of $c$ and $\lambda$. This is specific to our problem (a posteriori), and introduces extra paths (from $c'$ to $c$ and $\lambda$), but not cycles, in the directed graph or DAG of variable dependencies depicted below. These extra dependency paths are shown in green, while the original depenencies of $c(t,\lambda)$ are red, and all the rest, which follow from a priori principles (like the total derivative a.k.a. chain rule formula are black).

dependency graph for c, t, lambda and selected derivatives

Now from the (a priori) definition of total derivative, $$ \frac{d}{dt}f(c,\lambda) =f_cc'+f_\lambda\lambda' =ff_c+\lambda'f_\lambda $$ and $$ (c_t)'=c_{tt}+\lambda'c_{t\lambda} $$ so that (using the quotient rule) $$ \frac{d}{dt} \left( \frac{\partial c}{\partial \lambda} \right) = (c_\lambda)' = \left( \frac{f-c_t}{\lambda'} \right)' = \frac{ \left(f'-(c_t)'\right)\lambda' - \left(f-c_t\right)\lambda'' }{(\lambda')^2} $$ $$ =\frac{ \left(ff_c+\lambda'f_\lambda\right) -\left(c_{tt}+\lambda'c_{t\lambda}\right) -\lambda''c_\lambda }{\lambda'} $$ $$ =f_\lambda-c_{t\lambda} +\frac{ff_c-c_{tt}-\lambda''c_\lambda}{\lambda'} $$ Note that we did not need or use the equations $$(c_\lambda)'=c_{\lambda t}+\lambda'c_{\lambda\lambda}$$ $$(c')_t=c_{tt}+\lambda'c_{\lambda t}$$ but by the latter, we can see that $(c_t)'=(c')_t$ $\iff$ $c_{\lambda t}=c_{t\lambda}$ $\iff$ $c(t,\lambda)\in C^2$.

Also, note that

  • the answer would just be $(c_\lambda)'=c_{\lambda t}$, by the former equation above, if $\lambda$ were a model parameter so that $\lambda'=0$;
  • the answer would be quite different if $f$ were the partial, rather than the total, derivative of $c$, i.e. if we were given $\frac{\partial}{\partial t}c(t,\lambda)=f(c,\lambda)$ in the original problem.
share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.